DETERMINAN KEPUTUSAN PEMBELIAN PRODUK FASHION LOKAL BRAND ERIGO DI SHOPEE - Mahrizal, Mahrizal; Zulkifli, Zulkifli; Herizal, Herizal (Jurnal Riset Entrepreneurship, 2024)
Nowadays, development of technology is increasingly advanced, it is the main attraction for local and foreign entrepreneurs to invest in the industrial sector, one of which is in the fashion industry in Indonesia which has an important role in economic growth in the country. One strategy to grow the current buying and selling industry quickly is to sell products online on social media and e-commerce platforms used by the Erigo company. This study aims to examine and analyze the factors influencing of celebrity endorser, information quality and brand image on purchasing decisions of Erigo Brand product in Shopee. The quantitative and regression analysis were used as the research method in this study. The sample was obtained using a purposive sampling method and 70 respondents as a sample source was distribution online questionnaires via WhatsApp to Shopee users in Aceh. The data analyzed with Partial Least Squares-Structural Equation Modeling (PLS-SEM). The results of this study indicate that the celebrity endorser, information quality and brand image significantly influence on purchase decision in Shopee users. The finding of study can be a reference for future researchers who will study similar problems. The finding of study can be a reference for future researchers who will study similar problems related to the determining factors of the online purchasing decision process in marketplaces in Indonesia. It is hoped that the results of this research can help companies maintain brand image and provide quality information that can strengthen consumer trust so that the online shopping decision process continues to improve.